Sea Level Variations and their Relations to the Meteorological Factors in the Arab Gulf Area with Stress on Monthly Means - el-Gindy, A. A. H. (The International Hydrographic Review, 2015)
The hydrographic and meteorological conditions affecting the sea level in the Arab Gulf region have been reviewed. The monthly mean sea level data along the Saudi Arabian coast, relative to Indian Spring Low Water (ISLW) and the atmospheric pressure of eight years from 1980 to 1987 have been analysed spectrally. This indicated that the annual cycle is the main oscillation in both the sea level and pressure records. The oscillations with frequency less than 0.2 cycle/month were coherent. The Fourier analysis of six years data of monthly means showed that the annual cycle has an amplitude of 10-11 cm. The monthly mean sea level in the last two years was calculated using the harmonic simulation and the statistical models relating to the sea level and atmospheric pressure. The comparison between the calculated values and the observed ones in 1986 and 1987 showed reasonable agreement; the harmonic simulation deviated from the observations by about + 5 cm. The influence of the factors other than the atmospheric pressure on the sea level of the study area was found to be positive from June to December and negative from January to April or May, with maximum absolute value of about 11 cm, while the statistical models predict only the pressure effect.